From high school guidance to career contentment: assessing the impact of career intervention on subject choice and satisfaction. - Chen, Huaruo; Gu, Xueying (British Journal of Guidance & Counselling, 2025)
China's new college entrance examination reform is a major change in the history of education. This reform has returned the right of choice to students, but the existing studies propose subject selection solutions without providing systematic interventions and assessment tests. Therefore, a "double-loop" practice model is developed and applied to actual high school students' subject selection guidance, and its effectiveness and value are tested. According to the model, 544 high school students in Jiangsu Province, China, were selected to conduct an experimental study on subject selection guidance to explore the pre and post changes after receiving such guidance. The results showed that career education significantly reduced students' career decision-making difficulties in coping with the real-life challenges of subject selection, while effectively promoting students' short-term shift from superficial to deep learning motivation, forming a deep understanding of high school learning and enhancing their maturity in career development.